Study and Design of Pendulum Assisted Hand Water Pump - Khoteja, Rejsha; Mishra, Sandhya; Niraula, Sarad; Kunwar, Kshitij; Ghimire, Nirajan; Shrestha, Krishna Prasad; Shrestha, Pratisthit Lal (Kathmandu University Journal of Science, Engineering and Technology, 2021)
The designed pump consists of a normal hand pump and a pendulum, held together into a mechanism by a metal structure. This pendulum pump aims to provide a solution for lifting water manually, which requires a large human effort when operated continuously. It is based on a very simple principle of the pendulum, lever two-staged oscillator mechanism. With the help of this principle, the reciprocating motion of the piston in the pump is obtained using the oscillation of a pendulum. The pendulum pump was designed using different calculations and was fabricated adding frame, springs, pendulum to normal piston pump for the actual experimentation. The project purely deals with the mechanical aspect of the pendulum pump, where an experimental approach is implemented to conclude. The average discharge of water at 30°, 40°, 50° and 60° swing angles were 51ml, 59ml, 70ml, 98ml respectively which concluded that the discharge of this designed pump extremely depends on the swing angle of the pendulum as water discharge is increased with increasing angle as seen from experimentation. Also, from experimentation, this designed pump pumps out approximately 9% of more water than a conventional hand water pump taken average discharge of normal pump as reference under the same circumstances. As this pump can be operated with minimum effort compared to a normal hand pump, it can be operated by people of any age and even by physically challenged people. This machine can be useful for small scale irrigation, handling of wastewater, lifting water to small height for household purposes or to lift water from well.